Analisis perbandingan rencana strategis dalam perbankan: Studi kasus Bank CIMB Niaga Tbk., Bank Maybank Tbk., & Bank Seabank Indonesia Tbk - Rahmawati, Zulfa Muasaroh Binti; Lestari, Renita Diyana; Rengganis, Diaz Ayu (Maliki Interdisciplinary Journal, 2023)
This research aims to compare the strategic plans of three banks, namely PT Bank Maybank Indonesia Tbk, PT Bank Seabank Indonesia, and PT Bank CIMB Niaga Tbk. This research uses secondary data from various sources such as journals, reports and regulations. The research results show that the three banks have different strategic plans, depending on the goals and focus of each bank. PT Bank Maybank Indonesia Tbk focuses on developing digital banking services to increase non-interest income, while PT Bank Seabank Indonesia focuses more on developing products and services to increase customer satisfaction. Meanwhile, PT Bank CIMB Niaga Tbk focuses on business development and marketing, as well as employee development and company performance. Even though they have different focuses, the three banks have the same goal, namely to improve performance and business growth. In this case, a good and integrated strategic plan is very important to achieve this goal.